2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7510972
|View full text |Cite
|
Sign up to set email alerts
|

Massive MIMO relaying with hybrid processing

Abstract: Massive multiple-input multiple-output (MIMO) relaying is a promising technological paradigm which can offer high spectral efficiency and substantially improved coverage. Yet, these configurations face some formidable challenges in terms of digital signal processing (DSP) power consumption and circuitry complexity, since the number of radio frequency (RF) chains may scale with the number of antennas at the relay station. In this paper, we advocate that performing a portion of the power-intensive DSP in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Multiple antenna techniques offer potential benefits in wireless communications through their additional spatial degrees of freedom [19], [29], [30], which can be exploited to further enhance the performance of NOMA. The authors in [31] have investigated a beamforming design to maximize sum rate in a multiple-input single-output (MISO) NOMA system using the CCP method which is mainly based on the Taylor series approximation to transform the non-convex constraints into convex form.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple antenna techniques offer potential benefits in wireless communications through their additional spatial degrees of freedom [19], [29], [30], which can be exploited to further enhance the performance of NOMA. The authors in [31] have investigated a beamforming design to maximize sum rate in a multiple-input single-output (MISO) NOMA system using the CCP method which is mainly based on the Taylor series approximation to transform the non-convex constraints into convex form.…”
Section: Introductionmentioning
confidence: 99%
“…Speaking of designing analog precoding using phase shifters, the angle elements are usually quantized and selected from a finite-size codebook because most phase shifters are digitallycontrolled in current communication systems [11], [22], [28]. In this paper, the angle of each phase shifter is chosen from a codebook A = {e j2πn/2 B 1 , n = 0, 1, ..., 2 B 1 − 1} based on the minimum Euclidean distance criterion where B 1 represents the number of quantization bits for analog precoding per phase shifter.…”
Section: B Quantized Hybrid Precoding Designmentioning
confidence: 99%
“…[27] investigated the pilot design and feedback strategy for hybrid precoding architecture. In [28] [29], the quantized analog precoding was analyzed in hybrid processing for multiuser massive MIMO systems. For massive MIMO, [30] analyzed the performance of a limited feedback massive MIMO system.…”
Section: Introductionmentioning
confidence: 99%
“…Although the hybrid precoding has been widely considered in research, evidence has shown that it may not be the best choice for all cases compared with the pure analog precoding, especially when considering that analog precoding consumes less power than the hybrid precoding due to some implementation facts [4] [6]. In [7] [8], the analog precoding approximately transformed the effective channel into a diagonal matrix, which implies that digital processing is no longer needed for further multiuser interference cancellation.…”
mentioning
confidence: 99%